Transparency of the Booty Auction at the Jeneponto State Attorney - Nur, Andi Cudai; Erwin, Fitrah In Ramahani; Yamin, Muh Nur (Universitas Negeri Makassar, 2024)
This study aims to find out how the Transparency of Booty Auctions at the Jeneponto State Attorney's Office. To achieve the objectives of the study, researchers used data collection techniques through observation, interviews, and documentation. Data obtained from the results of the study were then processed by using qualitative analysis. The results of this study illustrate that transparency in the auction of loot at the Jeneponto District Attorney's Office has reached a good level, although there are still some aspects that require improvement. This assessment is based on the evaluation of indicators of openness of service processes and complaint mechanisms that have been running effectively. However, one aspect that requires more attention is related to the ease of access to information. There is low public awareness regarding the implementation of loot auctions, which is an indicator that efforts to increase public knowledge need to be improved. Therefore, the Jeneponto District Attorney's Office is advised to introduce innovations in disseminating information related to loot auctions, including the use of online-based platforms, to achieve wider openness and allow more people to be involved and file complaints related to the conduct of auctions. This will help strengthen transparency, participation, and accountability in the loot auction process.